Experiences and meanings on insecurity in Córdoba, Argentina: multi-sited approach to the relationship between mass media and their audiences - Morales, Susana María (2022)
The article analyzes the place of the media in the construction of experiences and meanings about insecurity, giving an account of findings and theoretical-methodological keys that contribute to the approach of the diffuse power of the media in this phenomenon. It is part of an investigation carried out in the city of Córdoba between 2016 and 2018, in which we inquire about the relationships between the media system, the transformations of the public space and the link between the police journalistic genre and the ways in which subjects experience insecurity. In methodological terms, it involved carrying out a multi-sited study that, from a socio-anthropological perspective, investigated the production, texts and reception of television news on insecurity broadcast by three air television channels in this city. In this way, we went through the different instances of articulation in the logic of production of meaning around insecurity in mediated societies.